EFL Students’ Perceptions on the Use of Google Meet in Online Learning During the Time of Coronavirus: A Literature Review - Tommy Hastomo; Hajjah Zulianti (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2021)
During the pandemic, the teaching and learning process is carried out by implementing e- learning or online learning. One of the most common applications that are used in online learning is Google Meet. The researchers focused on EFL students’ perception by looking for significant studies using information and communication technology using Google Meet for students' English learning during the pandemic. The data used in this literature review are published articles in the form of pdf format. Thus, a total of six studies were found relevant to review. The result showed that using Google Meet in online learning during the pandemic is helpful to assist their learning process. However, students still prefer face-to-face learning because online learning tends to get boring and uninteresting. After all, most teachers are incapable of using an online application to provide an engaging, creative, and innovative learning environment. Keywords: Students’ Perceptions, Google Meet, Online Learning, EFL.